Current state and development of police law as a subsystem of administrative law - O. A. Zhydovtseva (Bulletin of Kharkiv National University of Internal Affairs)
The aim of the article is to study the current state and prospects of police law as a subsystem of administrative law. It is determined that in the conditions of reforming the police as one of the law enforcement bodies of Ukraine, in particular reformatting the activities of this state body in accordance with European requirements, the study of police law is extremely important. Since police activities are also related to administrative processes, police law can be classified as a subsystem of administrative law. It is determined that despite the lack of legislative interpretation of the concept of "police law", today domestic law schools in the field of administrative law have formulated basic provisions on the nature, content and characteristics of police law as a sub-branch of administrative law. The main content of the police law structure as one of the sub-branches of administrative law is the legal norms that regulate the activities of the police and their internal organizational structure. Meanwhile, the study of problematic aspects of policing does not lose its relevance and importance, as such activities are primarily focused on respect for human and civil rights and freedoms, as well as the provision of services to the public. In order for legal norms to have an effective impact on police-citizen relations, legislation must meet the criteria of rationality and reasonableness. They should not create any gaps or conflicts in the legislation, which additionally indicate the need to further develop police law, which should be a solid foundation for the activities of each police department.